Immune Response and Immunotherapy in Chronic Lymphocytic Leukemia - Huergo-Zapico, Leticia; Gonzalez-Rodríguez, Ana P.; Contesti, Juan; Fernández-Guizán, Azahara; Huerta, Andrea Acebes; López-Soto, Alejandro; Gonzalez, Segundo (IntechOpen, 2012)
None